2020
DOI: 10.1038/s41389-020-00247-1
|View full text |Cite
|
Sign up to set email alerts
|

BRN2 expression increases anoikis resistance in melanoma

Abstract: Melanoma tumors are highly heterogeneous, comprising of many cell populations that vary in their potential for growth and invasion. Differential transcription factor expression contributes to these phenotypic traits. BRN2, a member of the POU domain family of transcription factors is thought to play important roles in melanoma invasion and metastasis. However, the function of BRN2 during the metastatic process of melanoma remains largely unknown. We therefore investigated the effect of BRN2 expression in melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Pierce et al found that overexpression of BRN2 can constrain melanoma proliferation and trigger partial resistance of melanoma cells to BRAFi. 47 TWIST1, a basic helix-loop-helix TF, controls melanoma cell invasion, and has recently been found to confer chemoresistance to various cancer cell types. [48][49][50] Another NC-associated gene, ZEB1, was identified as a master regulator of melanoma stemness and resistance toward BRAFi and MEKi.…”
Section: Discussionmentioning
confidence: 99%
“…Pierce et al found that overexpression of BRN2 can constrain melanoma proliferation and trigger partial resistance of melanoma cells to BRAFi. 47 TWIST1, a basic helix-loop-helix TF, controls melanoma cell invasion, and has recently been found to confer chemoresistance to various cancer cell types. [48][49][50] Another NC-associated gene, ZEB1, was identified as a master regulator of melanoma stemness and resistance toward BRAFi and MEKi.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies found that TyrRS could facilitate gastric cancer progression and homologous recombination process by regulating phosphatidylinositol 3-kinase (PI3K)/AKT signaling ( Zhang et al, 2020 ). Melanoma is a type of aggressive skin cancer with high heterogeneity ( Pierce and Simmons, 2020 ). WARS could regulate the proliferation, migration and invasion of uveal melanoma cells via inducing the activation of PI3K/AKT/mTOR pathway, suggesting that WARS might be is a novel tumorigenic factor ( Yang et al, 2020 ).…”
Section: Roles Of Arss In Cancermentioning
confidence: 99%
“…BRN2 has also been shown to repress MITF expression and mark a distinct subpopulation of MITF-negative melanoma cells. Furthermore, related to its role in promoting melanoma metastasis, BRN2 confers anoikis resistance and promotes metastatic growth after the dissemination of melanoma [ 26 , 27 ]. A separate study identified a previously undocumented role for BRN2 [ 28 ].…”
Section: Transcriptional Regulators In Melanomamentioning
confidence: 99%